Building Mamagement under Limate Change Condition for Mekong Delta in Vietnam - Le, Trung Phong (2020)
Recently climate change affect directly to the living condition of all households in Mekong delta of Vietnam. To be aligned with such condition, people are trying to build more building with higher level to maintain all floors above the sea level. However when the tide down their building is not sufficient for such dry condition. In this research the author propose a multi purposes building management to help them solving such problem. Beside that people can approach the clever manner with bad leaving condition in Vietnam.